2019
DOI: 10.1002/ett.3561
|View full text |Cite
|
Sign up to set email alerts
|

A leaky integrate and fire model for spike generation in a neuron with variable threshold and multiple‐input–single‐output configuration

Abstract: Comprehensive understanding of the phenomenon of spike transfer from one neuron to another in human brain is essential for developing spiking neuronal network models. Synapses play pivotal role in transferring information from one neuron to another. A leaky integrate and fire model of a representative neuron in multiple‐input and single‐output configuration with threshold variability for neuronal spike transfer process is proposed in this paper. A simple analytical expression of membrane potential including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Additionally, single-neuron calcium spikes and similar biophysical events have specialized nonlinear features that are leveraged by deconvolution methods to decode underlying voltage spikes by supervised learning of large amounts of data (18,19). Future variations of the method presented here will mimic specific signal properties relevant to biophysical processes and train over less naïve presynaptic input and signal shapes, as well as use leaky integrate and fire neurons more suitable for recreating tonic firing and bursting network activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, single-neuron calcium spikes and similar biophysical events have specialized nonlinear features that are leveraged by deconvolution methods to decode underlying voltage spikes by supervised learning of large amounts of data (18,19). Future variations of the method presented here will mimic specific signal properties relevant to biophysical processes and train over less naïve presynaptic input and signal shapes, as well as use leaky integrate and fire neurons more suitable for recreating tonic firing and bursting network activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows the Axon-Hillock circuit, which is considered to be the traditional artificial neuron circuit [19]. It was proposed by Mead in 1989 and has been widely used in many works [20,21]. The input current I in is commonly generated by a photodiode, in which different light intensities correspond to different magnitudes of the induced currents.…”
Section: The Principle Of Axon-hillock Circuitmentioning
confidence: 99%
“…Various research showed that the increase of variability of neuron threshold is proportional to the increasing in the input spikes firing rate [45]. Also, a few neuromorphic hardware was built to achieve the relationship between threshold and firing rate [39]. An experiment that had been performed in vivo showed that threshold variability plays a crucial role in the information transfer process in the brain of electric fish [46], [47].…”
Section: Related Workmentioning
confidence: 99%